Dharahara: A Multiple Times Earthquake Demolished Monument, Its Conservation Status - Gyawali, Prajeeta; Gyawali, Prajesh; Panth, Gaurav (Journal of Engineering Issues and Solutions, 2026)
This paper studies the changes that occur during the conservation of earthquake-demolished historical monuments in Nepal, taking “Dharahara” as an example. The tower has suffered extensive damage multiple times due to earthquake occurring in different time periods. Historical monuments respond differently during earthquake depending on the construction technology and materials used. When such monuments are destroyed, alterations in materials and technology are introduced during their reconstruction. The ancient monument Dharahara which was destroyed many times, was examined to understand how it was originally constructed, what materials were used, and what changes have been incorporated in its recent reconstruction. The purpose of this study is to highlight the importance of documenting and preserving Nepal’s unique construction techniques and materials for future generations. Data were collected through a review of relevant literature and analysis of existing documentaries. Information was also obtained from interviews with two historic researchers, followed by thematic analysis. The data were analyzed using constant comparison and contrast with international charters for conservation and restoration prepared by ICOMOS. Findings reveal that historical structures in Nepal were traditionally built with locally developed materials and techniques. However, modern reconstruction practices increasingly rely on new construction technologies. In the case of Dharahara, its authentic building methods and materials were not retained; only its form and appearance have been restored. Therefore, historical monuments should be thoroughly documented before reconstruction, and restoration efforts should aim to preserve their original features with minimal modification.